2021
DOI: 10.1101/2020.12.30.424861
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genetic depletion studies define receptor usage by virulent hantaviruses in human endothelial cells

Abstract: Hantaviruses are a large group of RNA viruses that include known epidemic threats and other agents poised for emergence. Several rodent-borne hantaviruses cause zoonoses accompanied by severe illness and death. However, assessments of zoonotic risk and the development of countermeasures alike are challenged by our limited knowledge of the molecular mechanisms of hantavirus infection, including the identities of cell entry receptors and their roles in influencing viral host range and virulence. Previous work ha… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Herein, we identified residues in the EC1 domain of PCDH1 critical for ANDV and SNV Gn/Gc engagement, including one that influences cellular host range, and demonstrated that Gn/Gc:PCDH1 recognition, not just PCDH1 per se , is required for development of lethal ANDV infection in Syrian hamsters. We conclude that PCDH1 is a bona fide entry receptor for ANDV and SNV, the primary etiologic agents of HCPS in the Americas, and is likely to play such a role for other New World hantaviruses shown to utilize PCDH1 for entry (6,32).…”
Section: Discussionmentioning
confidence: 87%
“…Herein, we identified residues in the EC1 domain of PCDH1 critical for ANDV and SNV Gn/Gc engagement, including one that influences cellular host range, and demonstrated that Gn/Gc:PCDH1 recognition, not just PCDH1 per se , is required for development of lethal ANDV infection in Syrian hamsters. We conclude that PCDH1 is a bona fide entry receptor for ANDV and SNV, the primary etiologic agents of HCPS in the Americas, and is likely to play such a role for other New World hantaviruses shown to utilize PCDH1 for entry (6,32).…”
Section: Discussionmentioning
confidence: 87%